2023
DOI: 10.3390/polym15020307
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Polymerisation of D-Limonene and Its Antimicrobial Activity

Abstract: Antibacterial coating is necessary to prevent biofilm-forming bacteria from colonising medical tools causing infection and sepsis in patients. The recent coating strategies such as immobilisation of antimicrobial materials and low-pressure plasma polymerisation may require multiple processing steps involving a high-vacuum system and time-consuming process. Some of those have limited efficacy and durability. Here, we report a rapid and one-step atmospheric pressure plasma polymerisation (APPP) of D-limonene to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…The oxygen O 1s peaks in the CaCrO 4 sample are shown in Figure b, and the observable peaks in the O 1s binding energy region were found to be 530.6 and 531.8 eV, respectively. A similar study has been reported in the literature. , The high-resolution XPS spectra that were employed to verify the valence state of the Cr species within the CaCrO 4 structure are shown in Figure c. The Cr 2p spectrum was deconvolved into four peaks, and the best fit was obtained.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…The oxygen O 1s peaks in the CaCrO 4 sample are shown in Figure b, and the observable peaks in the O 1s binding energy region were found to be 530.6 and 531.8 eV, respectively. A similar study has been reported in the literature. , The high-resolution XPS spectra that were employed to verify the valence state of the Cr species within the CaCrO 4 structure are shown in Figure c. The Cr 2p spectrum was deconvolved into four peaks, and the best fit was obtained.…”
Section: Resultsmentioning
confidence: 64%
“…A similar study has been reported in the literature. 35 , 36 The high-resolution XPS spectra that were employed to verify the valence state of the Cr species within the CaCrO 4 structure are shown in Figure 7 c. The Cr 2p spectrum was deconvolved into four peaks, and the best fit was obtained. The Cr 2p spectrum contains two doublets, 2p 3/2 and 2p 1/2 , Peaks at 576.4 and 586.5 eV were attributed to Cr (III) 2p 3/2 and 2p 1/2 , respectively, while peaks at 579.9 and 588.9 eV were assigned to Cr (III) 2p 3/2 and Cr (III) 2p 1/2 , respectively (VI).…”
Section: Resultsmentioning
confidence: 99%
“…The XPS survey scan results revealed a standard carbon C 1 s peak at about 285 binding energy. After ppCar, the corresponding binding energies were used to component-fit the carbon C1s peaks: C-H/C-C is 285.0 eV (hydrocarbons), C-O-C/C-N/C-OH is 286.3 eV (hydroxyl or ether), N-C=O/C=O is 287.6 eV (carbonyl) and O-C=O is 288.8 eV (carboxyl) [ 32 ]. These XPS bonds confirm the presence of the plasma-polymerised carvone (ppCar) thin film.…”
Section: Resultsmentioning
confidence: 99%
“…In order to bind these antibacterial precursor materials, several coating strategies have been investigated for this purpose, such as atom transfer radical polymerization (ATRP) [10], self-assembled monolayers (SAMs) [11], and layer-by-layer deposition [12], as well as plasma polymerization or plasma treatment [13,14]. Particularly, plasma treatment and plasma polymerization are emerging techniques that can be distinguished from each other based on the utilization of an organic precursor in the latter process, which deposits a film of polymeric coating onto the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting products, including reactive species and nonreactive ones, were deposited onto the chosen substrate, where adsorption and surface reactions occurred at the same time. Several published studies have investigated the antibacterial properties of various non-carvone coatings produced by this APPJ process [13,17].…”
Section: Introductionmentioning
confidence: 99%